Engineered protein containing crotoxin epitopes induces neutralizing antibodies in immunized rabbits. (March 2020) - Molina Molina, Denis A.; Guerra-Duarte, Clara; Costal-Oliveira, Fernanda; Almeida Rocha, Elizângela; Rego Rodrigues, Carolina; Machado-de-Ávila, Ricardo A.; Soccol, Vanete T.; Chávez-Olórtegui, Carlos
Graphical abstract: Highlights: Five crotoxin epitopes were mapped by peptide arrays. All epitopes sequences were combined to form a single recombinant multiepitopic protein (rMEPCtx). Anti-rMEPCtx serum cross-reacted with C.d.terrificus, C.d.ruruima, Peruvian C. durissus and B.jararaca snakes venoms. Anti-rMEPCtx serum efficiently neutralized the lethal activity of crotoxin from C. d terrificu venom. rMEPCtx could be an alternative antigen to the production of immunotherapeutics. Abstract: Crotoxin (Ctx) is the main lethal component of Crotalus durissus terrificus venom. It is a neurotoxin, composed of two subunits associated by noncovalent interactions, the non-toxic acid subunit (CA), named Crotapotin, and the basic subunit (CB), with phospholipase A2 (PLA2 ) activity. Employing the SPOT synthesis technique, we determined two epitopes located in the C-terminal of each Ctx subunit. In addition, 3 other epitopes were mapped in different regions of Ctx using subcutaneous spot implants surgically inserted in mice. All epitopes mapped here were expressed together as recombinant multi-epitopic protein (rMEPCtx), which was used to immunize New Zealand rabbits. Anti-rMEPCtx rabbit serum cross-reacted with Ctx and crude venoms from C. d. terrificus, Crotalus durissus ruruima, Peruvian C. durissus and Bothrops jararaca (with lower intensity). Furthermore, anti-rMEPCtx serum was able to neutralize Ctx lethal activity. As the recombinant multiepitopic protein is not toxic, it can be administered in larger doses without causing adverse effects on the immunized animals health. Therefore, our work evidences the identification of neutralizing epitopes of Ctx and support the use of recombinant multiepitopic proteins as an innovation to immunotherapeutics production.